Theories of Development Concepts and Applications - Crain, William (CRC Press, 2024)
Theories of Development introduces students to the most influential theorists who have contributed to our understanding of how we develop as individuals. The book focuses on the theorists who have built upon the developmental tradition established by Rousseau, along with other theorists, including ethologists and psychoanalysts, who share a developmental outlook. It considers the different concepts they present along with their practical implications, whilst also discussing the ways in which developmental theorists have anticipated and advanced humanistic ideas and insights.This edition has been thoroughly updated throughout, and now includes:• A new chapter comparing treatment approaches to autism• Greater attention to Erikson’s theory of identity formation and how it pertains to gender issues• New thoughts on cultural factors in Piaget’s theory• Biographical material on Jane Goodall, Howard Thurman, and Albert Einstein that illustrate developmental processesDemonstrating how we might view the world differently at various stages of life, Theories of Development is a must-read for all students of psychology and education